2012
DOI: 10.4103/1817-1737.102182
|View full text |Cite
|
Sign up to set email alerts
|

Relation of oxidant-antioxidant imbalance with disease progression in patients with asthma

Abstract: CONTEXT:Asthma is a chronic airway disorder which is associated to the inflammatory cells. Inflammatory and immune cells generate more reactive oxygen species in patients suffering from asthma which leads to tissue injury. AIMS:To investigate the role of oxidant-antioxidant imbalance in disease progression of asthmatic patients.SETTINGS AND DESIGN:In this study, 130 asthmatic patients and 70 healthy controls were documented.METHODS:For this malondialdehyde level, total protein carbonyls, sulfhydryls, activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 48 publications
1
33
1
1
Order By: Relevance
“…It was also observed that resting or stimulated phagocytes may produce differently reactive oxygen species that depends on the disease form [27]. Predominance of enhancement of ROS has been observed in asthma [25-27]. The differences between our observations and other researchers who have assessed ROS in asthma are most likely the result of the type of ROS evaluated, the cell type assessed and differences in the clinical form and severity of the disease.…”
Section: Discussionmentioning
confidence: 40%
“…It was also observed that resting or stimulated phagocytes may produce differently reactive oxygen species that depends on the disease form [27]. Predominance of enhancement of ROS has been observed in asthma [25-27]. The differences between our observations and other researchers who have assessed ROS in asthma are most likely the result of the type of ROS evaluated, the cell type assessed and differences in the clinical form and severity of the disease.…”
Section: Discussionmentioning
confidence: 40%
“…The activity of SOD is as an intracellular antioxidant enzyme. SOD activity in the asthmatic patients was lower than that in the healthy controls [14]. The mechanism of oxidative stress in asthma remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…Exposure to air pollutants can lead to oxidative stress in the airways, and there is compelling evidence that asthmatic airways are deficient in antioxidant defenses 89 . Furthermore, the antioxidant capacity of the lungs is inversely related to asthma severity 90 . In addition to lower levels of superoxide dismutase and catalase, 89 it has been shown that goblet cells express the high-affinity sodium ascorbate cotransporter, which is involved in vitamin C uptake into cells, and that expression of sodium ascorbate cotransporters is inversely related to lung lining fluid vitamin C levels 91 .…”
Section: Dysregulation Of the Epithelial Barrier In Asthmatic Patientsmentioning
confidence: 99%